2003
DOI: 10.1097/00012272-200304000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Preadolescents With ADHD

Abstract: This study tested the clinical utility of the Frame Model of Preadolescent Empowerment as a means of enhancing the self-perception of children diagnosed with attention-deficit hyperactivity disorder (ADHD). The intervention, which has theoretical roots in Roy's Adaptation Model, Harter's Developmental Perspective, and Murrell-Armstrong's Empowerment Matrix, was administered to children with ADHD in a pretest/posttest design. Findings indicate that this model significantly increased the perceptions of self-wort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This literature asserts how empowering characteristics such as patient decision‐making, effective dialogue between clinicians and patients, and coping skills, showed effective illness management, improved health behaviours, and mental health outcomes. These findings were also apparent in studies which focused on empowerment and health outcomes for individuals with chronic mental illness (Frame, ; Lorig, Sobel, Ritter, Lauren, & Hobbs, ; Lorig, Ritter, et al ., ; Melnyk et al ., ; Rosenfield, ). This literature demonstrates the positive impact of empowerment on one's self‐efficacy, confidence, self‐esteem, motivation, personal control, critical awareness, ability to problem solve, and skills development.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This literature asserts how empowering characteristics such as patient decision‐making, effective dialogue between clinicians and patients, and coping skills, showed effective illness management, improved health behaviours, and mental health outcomes. These findings were also apparent in studies which focused on empowerment and health outcomes for individuals with chronic mental illness (Frame, ; Lorig, Sobel, Ritter, Lauren, & Hobbs, ; Lorig, Ritter, et al ., ; Melnyk et al ., ; Rosenfield, ). This literature demonstrates the positive impact of empowerment on one's self‐efficacy, confidence, self‐esteem, motivation, personal control, critical awareness, ability to problem solve, and skills development.…”
Section: Introductionmentioning
confidence: 78%
“…The importance of empowerment in relation to mental health from an adult perspective is well documented (Brosnan, ; Frame, ; Garcia, Vasiliou, & Penketh, ; Harper & Speed, ; Pitt et al ., ; Starkey, ; WHO, ; Woodall et al ., ), but far less understood from the perspective of young people. Current conceptual definitions of empowerment are derived from research with adults and are problematic when applied to young people experiencing mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…ADHD is a neurological disorder that affects adaptive functioning related to the impairment of four executive neuropsychological abilities: working memory, self-regulation of affect, motivation arousal, and internalization and reconstitution of speech (Barkley, 2006; Wu, Anderson, & Castiello, 2002). ADHD is characterized by behavioral symptoms of inattention, hyperactivity, and impulsivity as a persistent pattern throughout the life span which occurs across multiple settings (Barkley, 2006; Biederman, 2005; Diamantopoulou, Henricsson, & Rydell, 2005; Frame, 2003). Those who are diagnosed with ADHD are a heterogenic group and may have comorbidity with oppositional defiant disorder, conduct disorder, mood disorder, and anxiety (Biederman, 2005).…”
mentioning
confidence: 99%
“…Empowerment interventions, often consisting of support groups, educational opportunities, caregiver empowerment, patient decision-making, changes in health care services and advocacy efforts, have been actively pursued in diabetes care and other chronic diseases (110)(111)(112)(113)(114)(115) (109,(123)(124)(125). Self-management education for diabetes patients has shown impact through two systematic reviews; eleven studies of group-based education found improvements in diabetes control, knowledge and need for medication, associated with increased self-empowerment, self-management skills and treatment satisfaction (126).…”
Section: Patient or Consumer Empowerment Strategiesmentioning
confidence: 99%